The experiences of mothers who were implementing Kangaroo Mother Care (KMC) at a Regional Hospital in KwaZulu- Natal - J. Reddy; P.A. Mclnerney (AOSIS, 2007)
Kangaroo Mother Care (KMC) is a fairly new concept to the patients and personnel in the neonatal units in KwaZulu-Natal. Arising from one of the Governmental initiatives, KMC was introduced to KwaZulu Natal in 2001. The personnel at the regional hospital where this study took place, were briefly introduced to this alternate method of care for a low birth weight baby, by means of symposia and in-service training. This study was undertaken to explore the perceptions of mothers for the preparation and experience of KMC and to describe the experiences of the mothers who had implemented KMC. Furthermore, this study sought to determine whether mothers received support during the implementation of KMC and if so, to identify the sources of this support. The lack of documented evidence to problems that mothers may have encountered and management strategies to deal with these, prompted the study. A phenomenological approach was used. The sample was obtained from the neonatal unit of a regional hospital in Durban. The sample comprised of ten mothers who were practicing KMC in the post-natal ward, or mothers who were discharged and were still practicing KMC. Data were collected by means of face-to-face interviews. These interviews provided the researcher with rich, personal and narrative experiences of the carers before and during KMC. The results of this study indicated that KMC was indeed new to most of the mothers and this evoked apprehension, doubt and fear, but once the mothers had tried it and were successful, they felt a sense of joy. Nursing personnel formed part of the supportive environment for the mothers practicing KMC. Recommendations are made for nursing practice, nursing education and nursing research.